2014
DOI: 10.1080/01434632.2014.884099
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cross-cultural communication education on international students' adjustment and adaptation

Abstract: The recent increase in the provision of cross-and intercultural education for sojourners has not been matched by commensurate research into its effects on participants. Evaluation, where undertaken at all, has been largely confined to expatriate business contexts and has tended to be undertaken pre-sojourn. Crucially, evaluation has not engaged with the adaptation, adjustment and performance of sojourners related to their actual lived experience of adjustment, or with any key outcomes of sojourns. In response,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 30 publications
2
43
0
1
Order By: Relevance
“…In addition to the ambiguity of findings from the short-term undergraduate study abroad context, little is known about the development of IC among postgraduate students studying abroad for a full degree (Young and Schartner 2014). This is despite an acknowledgement in the literature that the experiences of these 'vertically mobile' (OECD 2009) students can be vastly different, for a variety of reasons, from those of their peers on short-term study abroad schemes (e.g.…”
Section: Study Abroad and Intercultural Competencementioning
confidence: 97%
See 4 more Smart Citations
“…In addition to the ambiguity of findings from the short-term undergraduate study abroad context, little is known about the development of IC among postgraduate students studying abroad for a full degree (Young and Schartner 2014). This is despite an acknowledgement in the literature that the experiences of these 'vertically mobile' (OECD 2009) students can be vastly different, for a variety of reasons, from those of their peers on short-term study abroad schemes (e.g.…”
Section: Study Abroad and Intercultural Competencementioning
confidence: 97%
“…Recent research has shown that intercultural education plus the experience of 'living abroad' can create optimal conditions for IC development in international students (e.g. Behrnd and Porzelt 2012;Young and Schartner 2014). Courses in inter-and CCC, 5 where 'active processing' (Peckenpaugh 2012, 145) of intercultural encounters can take place, should therefore be increasingly offered to students undergoing a sojourn experience.…”
Section: Implications For Intercultural Education and Trainingmentioning
confidence: 98%
See 3 more Smart Citations